Distrectual osteosarcopenia in limb disuse: case report and mini literature review - Filoni, Gabriele; Di Lonardo, Michele; Mandile, Giovanni; Andreani, Lorenzo; Falossi, Francesca; Franchi, Alessandro; Bottai, Vanna; Capanna, Rodolfo (Acta Biomedica Atenei Parmensis, 2020)
Osteosarcopenia is a new concept of association of osteoporosis and sarcopenia. Both of these pathologies are more frequent in old people and general affects all the skeleton with increased risk of falls and fractures, loss of global function, fragility, and mortality, but also surgical failures.The coexistence of these condition derives from a close relationship, not only anatomical, between bone and muscle tissues. Sometimes these pathological conditions can involve only a skeleton segment, due to local disuse, causing a district form of sarcopenia. In this clinical case, Authors describes a case of isolated lower limb osteosarcopenia in a young non-osteoporotic patient, due to a prolonged limb disuse, complicated by surgical treatment failure for previous pathology, diagnosed by clinical, laboratory, instrumental and histopathological exams.